2009
DOI: 10.1002/jcp.21796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of growth inhibition by MicroRNA 145: The role of the IGF‐I receptor signaling pathway

Abstract: MicroRNA 145 (miR145) has been proposed as a tumor suppressor. It was previously shown that miR145 targets the 3' UTR of the insulin receptor substrate-1 (IRS-1) and dramatically inhibits the growth of colon cancer cells. miR145 also targets the type 1 insulin-like growth factor receptor (IGF-IR). We show here that an IRS-1 lacking its 3' UTR is no longer down-regulated by miR145 and rescues colon cancer cells from miR145-induced inhibition of growth. An IGF-IR resistant to miR145 (again by elimination of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 41 publications
7
88
0
Order By: Relevance
“…7 The cells seemed to stop growing, an observation that was confirmed in 3T3 cells transfected with mir145. 10 This is compatible with downregulation of IRS-1. There are normal cells and many cell lines that do not express IRS-1, or express very low levels, and these cells grow in 10% serum, although they are prone to differentiation (reviewed in ref.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…7 The cells seemed to stop growing, an observation that was confirmed in 3T3 cells transfected with mir145. 10 This is compatible with downregulation of IRS-1. There are normal cells and many cell lines that do not express IRS-1, or express very low levels, and these cells grow in 10% serum, although they are prone to differentiation (reviewed in ref.…”
Section: Introductionmentioning
confidence: 62%
“…The finding by LaRocca et al 10 that an IRS-1 without its 3'UTR rescues HCT116 ex5 cells from miR145-induced growth arrest was surprising. Most, if not all miRs have multiple targets, according to the databases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, miR-145 is a widely accepted tumor suppressor in human cancers and targets various oncogenes in cancer cells. 17,18,23,24 The miRNA signature described here includes approved miRNAs that are downregulated in human cancers, including PCa, and indicates the effectiveness of this signature for cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…Through functional studies, miR-145 has shown the dual tumor-suppressive and oncogenic phenotypes in different cell lines and animal models. miR-145 suppresses tumor cell growth by targeting insulin receptor substrate-1 (45), type I insulin-like growth factor receptor (46), and c-Myc (47). Meanwhile, miR-145 impacts the migration, invasion, and metastasis of cancer cells by targeting mucin 1 (48) and N-cadherin (49), and also affects p53-mediated cell-cycle arrest by targeting p21 (47).…”
Section: ) Ets1 Is Also Implicated In Vascularizationmentioning
confidence: 99%